Shelf life and presence of pathogens in liquid-smoked skipjack pampis packed in vacuum packaging (vp), modified atmosphere packaging (map), and stored at ambient temperature. - Mentang, Feny; Montolalu, Roike Iwan; DIEN, Henny Adeleida; MEKO, Ayub; BERHIMPON, Siegfried (Nutrición Clínica y Dietética Hospitalaria, 2022)
Skipjack pampis, a typical seafood dish from Manado, North Sulawesi, is made from smoked Skipjack (Katsuwonus pelamis L.). Our earlier research showed that adding liquid smoke (LS) to smoked skipjack considerably reduced the amount of benzo(a)pyrene in the fillet while also enhancing its sensory qualities. The study tried to examine the shelf life and presence of pathogens in LS Skipjack pampis stored in modified atmosphere packaging (MAP) and vacuum packaging (VP) with 100% N2 for 75 days at room temperature. At 0, 3, 6, 9, 25, 50, and 75 days of storage, microbiological and organoleptic characteristics were noted. Samples were analyzed at 0, 3, 6, 9, 25, 50, and 75 days for water content, pH, total plate count (TPC), and pathogenic bacteria (coliform, E. coli, Salmonella sp, and vibrio). Sensory analysis such as appearance, flavor, taste, and texture has also been determined using the Triangle test. We found that the TPC of Skipjack pampis kept in a 7.8 x 103 CFU/g VP and 7.0 x104 CFU/g MAP were still good for 25 days but rose significantly at 50 d and 75 days in the sample which used the MAP method. However, the samples that were packed in VP were still acceptable after 50 days (6.9 x 104 CFU/g) and 75 days (9.9 x 104 CFU/g). The flavor, taste, and odor could still be tolerated in VP until 75 days of storage while in MAP, the products were just acceptable only 25 days of being kept. Pathogenic bacteria were not found in the analyzed samples. The results showed that vacuum packaging was better than MAP for Cakalang pampis.